Nigerian Political Elites and the Covid-19 Pandemic’s Management Deficits: Implications for National Economic and Sustainable Development - Olawale Olufemi Akinrinde (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2021)
The impact of the novel covid-19, otherwise known as the corona-virus on the entire spectrum of Nigeria’s national life, as elsewhere, remains yet indelibly unquantifiable at present. No thanks to the Elite culpability in the management of the corona-virus epidemic that has now rendered the entire Nigeria’s national life halted and, on the brinks of spontaneous discontinuity. Conceptualized in this study to mean negligence of duty, this study unpacks howthe Nigerian political Elites and leadership’s inefficiency has contributed inversely to the eventual outbreak, sporadic rise and the negative consequences of Covid-19 on the entire populations’ Nigeria’s economic and sustainable development goals.Drawing from David Hume’s theory of causation, this study discovers that leadership and Nigerian political elites’ failure in the management of the Covid-19 pandemic, before and during its eventual outbreak and manifestation in Nigeria triggered the incident Covid-19 case in Nigeria, and its manifold effects on Nigeria’s prospects for the actualization of her economic and sustainable development pursuits.